A numerical approach for the combined analysis of the dynamic thermal behaviour of an entire ceramic roller kiln and the stress formation in the tiles. (15th June 2019) - Milani, M.; Montorsi, L.; Venturelli, M.; Tiscar, J.M.; García-Ten, J.
Abstract: The numerical analysis of thermal and fluid dynamics behaviour of an industrial roller kiln used for manufacturing ceramic tiles is carried out and combined with the analysis of the mechanical stresses formed in the final ceramics product. The developed numerical approach is able to address the energy efficiency, the fuel consumption as well as the pollutant emissions and the quality of the final product. The model of the ceramic kiln is based on a lumped and distributed parameter model and accounts for the heat and mass transfer phenomena that take place in the real components under actual operating conditions of the systems. Models for the simulation of the different components that are used for the kiln functioning are included in the modelling, such as the burners, the fan, the valves and the control system. The numerical approach demonstrates to predict accurately the temperature distribution of both the tiles and the hot gases along the kiln length. Numerical results are validated against experimental measurements carried out on a real kiln during regular production operations. Additionally, the calculated temperature profile of the tiles is employed to predict the mechanical stresses that form in the ceramic product within the kiln. A thermomechanical model is adopted to determine the curvature and residual stresses in the tiles and particular care is devoted to the final stresses that remain at the end of the kiln since they affect the quality of product. The developed numerical approach demonstrates to be an efficient tool for investigating different control strategies to optimize the kiln thermal behaviour as well as the tile quality. On the basis of the fluid-dynamics and thermomechanical numerical approaches, a modified operating strategy for the kiln's cooling section is proposed to minimize the tiles' residual stresses and the modified cooling profile resulted to be in the operating range of the real kiln. Highlights: The thermo-fluid dynamics model of an entire ceramic kiln is constructed The thermo-mechanical modelling for the stresses formation in ceramic tiles A combined approach is proposed to optimize the kiln control strategy The kiln operations to achieve the optimal cooling profile are calculated The residual stresses of the product is reduced to one fourth of the original value